Can Online Communication Prevent Depression Among Older People? A Longitudinal Analysis. (January 2022) - Nakagomi, Atsushi; Shiba, Koichiro; Kondo, Katsunori; Kawachi, Ichiro
Evidence on the association between internet usage and incidence of depression remains mixed. We examined the associations between different categories of internet usage and developing clinical depression. We used data from the 2013 and 2016 waves of the Japan Gerontological Evaluation Study (JAGES) comprising 12, 333 physically and cognitively independent adults aged ≥65 years. Participants were engaged in seven categories of internet usage: communication with friends/family, social media, information collection about health/medicine, searching for medical facilities, purchase of drugs and vitamins, shopping, and banking. We found that internet use for communication had a protective influence on the probability of developing clinical depression defined as the Geriatric Depression Scale scores ≥5 or self-reported diagnosed depression. Our findings support the role of online communication with friends/family in preventing clinical depression among older people. Online communication could be particularly useful in the COVID-19 crisis because many families are geographically dispersed and/or socially distanced.